Seroprevalence of Asymptomatic Dengue Virus Infection and Its Antibodies Among Healthy/Eligible Saudi Blood Donors: Findings From Holy Makkah City. Issue 1 (22nd February 2017) - M Ashshi, Ahmed; Alghamdi, Saad; El-Shemi, Adel G; Almdani, Sabir; Refaat, Bassem; Mohamed, Amr M; Ghazi, Hani O; Azhar, Esam I; Al-Allaf, Faisal A
Background: Threat to blood transfusion–transmitted dengue virus (DENV) and its antibodies has recently emerged worldwide. Dengue fever is an endemic disease in Saudi Arabia, particularly in its Western region. The aim of this study was to estimate the seroprevalence of asymptomatic DENV infection and its antibodies among eligible Saudi blood donors. Methods: Serum samples from 910 healthy/eligible adult male Saudi blood donors, who reside in Holy Makkah City of Saudi Arabia, were collected between March 2015 and August 2016 and screened for the detection of DENV nonstructural protein 1 (NS1) antigen and anti-DENV IgM and IgG antibodies using commercial enzyme-linked immunosorbent assay kits (Panbio, Brisbane, QLD, Australia). Results: Among the tested donors, 48 (5.3%) were seropositive for DENV-NS1 antigen, whereas 50 (5.5%) and 354 (38.9%) were seropositive for anti-DENV IgM and IgG antibodies, respectively. Seropositivity for DENV-NS1 antigen and/or anti-DENV IgM antibody among the tested donors reflects their ongoing asymptomatic viremic infectious stage with DENV during their donation time, whereas high prevalence of anti-DENV IgG seropositivity reflects the high endemicity of dengue disease in this region of Saudi Arabia. Conclusions: These results show high prevalence of asymptomatic DENV infection and its antibodies among Saudi blood donors, raising the importance of establishing blood screening for dengue disease at different blood donation services and units in Saudi Arabia to improve the guarantee of blood transfusions and to control DENV dissemination.